Análisis del impacto a las exportaciones de rosas en el Ecuador durante la pandemia sanitaria covid-19, como de estudio de la florícola, ASL FINE FLOWERS - Saransig Toctaquiza, Melany Paulina (2024)
The Covid 19 pandemic had a definitive social, political and economic impact on a global scale. The consequences were felt, without precedent, by the present generations. Many died as a result of this infection. Others, less affected, but just as affected, lost their jobs or their businesses closed down. The world economy suffered. The impacts of this on the world economy and on Ecuador are the subject of this study, more specifically the effects that occurred in Ecuadorian flower companies, taking as a reference the company ASL FINE FLOWERS. To determine the impacts, a qualitative analysis will be made of the variables in five areas of the company: 1, exports\; 2, human resources\; 3, production inputs\; 4, logistics\; and, 5, financing. The first will attempt to determine the impact on Gross Sales, Production Volume and International Customers. HR will focus on the impact on employees in the administrative and operational areas. The same will be determined in the area of inputs, logistics and financing. Finally, by way of conclusion, the impact of the COVID 19 pandemic on Ecuadorian flower companies, especially ASL FINE FLOWERS, will be clearly and precisely determined.